Adult T cell leukaemia/lymphoma (ATL) in pregnancy: A UK case series. Issue 1 (25th November 2020) - Motedayen Aval, Leila; Boullier, Mary; Lyall, Hermione; Collins, Graham P.; Ayto, Robert; Kelly, Dominic F.; Tedder, Richard S.; Drysdale, Simon B.; Taylor, Graham P.; Cook, Lucy B.
Abstract: Introduction: Chronic infection with human T‐cell lymphotropic virus type‐1 (HTLV‐1) may result in aggressive adult T‐cell leukaemia/lymphoma (ATL) in 4‐6% carriers. The majority of this risk arises in carriers infected during infancy, and so each infant has ∼25% lifetime risk. Other risk factors include a family history of ATL. Antenatal HTLV‐1 screening is not undertaken in the UK. Methods: Here we describe four cases of ATL diagnosed during pregnancy and describe strategies to minimise HTLV‐1 transmission to neonates. Results/conclusion: These cases highlight undiagnosed HTLV‐1 in pregnancy which allows ongoing mother to child vertical transmission and risk of future ATL. We recommend the UK National Screening Committee incorporate HTLV‐1 serology into antenatal screening.